Europe’s Economic Crisis: Re - Clustering European Economies (European Journal of Formal Sciences and Engineering, 2023)
National debt and distressed banks in countries such as Greece led to an ongoing recession since the beginning of Europe’s economic crisis. At the same time, austerity measures, all over Europe, reshape economies in a trial to increase global competitiveness. Economic integration as a challenge for social prosperity seems more crucial than ever, while it is a matter of research whether the acquired economic policies lead to further divergence. The paper explores how economic crisis has affected 40 European economies, by using macroeconomic indexes. A re-clustering of these economies is attempted for detecting similarities and differences between European economies. The analysis reveals how close an economic integration is and how a multi – speed European economy would look like today. Moreover, it explores how European economies have transformed during the last five years, in terms of competitiveness’ similarities and how the Gross National Income is related with governance indicators.
Keywords: European Economies, Multi – Speed Europe, European Integration, Competitiveness, Gross National Income per Capita, Economic Convergence, Welfare.